MANAJEMEN RANTAI PASOK KOMODITAS TELUR AYAM KAMPUNG - Saptana Saptana; Tike Sartika (Jurnal Manajemen & Agribisnis, 2014)
ABSTRACTThe studied aimed to formulate an integrated policy of supply chain management development of native chicken eggs. In detail, the research objectives were: 1) to describe the actors of supply chain of native chicken eggs, 2) to analyze the Institutions of supply chain management of native chicken eggs, and 3) to analyze the value chain of native chicken eggs. The data were obtained from interviewed with breeder of native chicken and group discussion with actors of supply chain in the province of West Java, East Java and South Kalimantan. Quantitative data were analyzed using analysis of R/C ratio, marketing margin system and value chain analysis, while qualitative information with a descriptive analysis was focus on institutions of supply chain management. The results showed that: 1) The eight main actors in supply chain of native chicken eggs commodity were: government, breeding industry, breeders, farmers groups, associations of farmers groups, traders at the centers of production, traders at the centers of consumption, and industrial of cake/bread; 2) most strategic institutional in the whole of supply chain of native chicken eggs was the institutionalization of distribution and marketing, and 3) cake/ bread industrial received the largest of value-added per unit of output, while the large traders in the center of production and consumption received the greatest value in the aggregate. The overall study of policy recommendations of `the development of agribusiness of native chicken eggs was the integration of all factors connected in supply chain.Keywords: institutional , agribusiness, value chain, eggs, economic sociaty   ABSTRAKSecara umum penelitian ini bertujuan merumuskan kebijakan pengembangan manajemen rantai pasok komoditas telur ayam  kampung secara terpadu. Secara rinci tujuan penelitian adalah 1) mendeskripsikan pelaku  rantai pasok komoditas telur ayam  kampung; 2) menganalisis kelembagaan manajemen rantai pasok komoditas telur ayam  kampung; dan 3) menganalisis rantai nilai komoditas telur ayam  kampung. Data yang digunakan bersumber dari hasil wawancara terstruktur dengan peternak ayam  kampung petelur serta wawancara kelompok dengan para pelaku rantai pasok di Provinsi Jawa Barat, Jawa Timur, dan Kalimantan Selatan. Data kuantitatif dianalisis menggunakan analisis R/C ratio, margin tata niaga dan analisis rantai nilai, sementara informasi kualitatif dengan analisis deskriptif dengan fokus pada kelembagaan manajemen rantai pasok. Hasil penelitian menunjukkan bahwa: 1) terdapat delapan pelaku utama rantai pasok komoditas telur ayam  kampung,  yaitu pemerintah, industri perbibitan, peternak, kelompok peternak, asosiasi peternak, pedagang di sentra produksi, pedagang di sentra konsumsi, dan industri kue/roti; 2) kelembagaan yang paling strategis dalam keseluruhan rantai pasok komoditas telur ayam  kampung adalah kelembagaan distribusi dan pemasaran; dan 3) industri kue/roti menerima nilai tambah terbesar per  unit output, sedangkan pedagang besar di pusat produksi dan pedagang besar di pusat konsumsi menerima nilai terbesar secara agregat. Rekomendasi kebijakan yang dihasilkan adalah pengembangan agribisnis komoditas telur ayam  kampung harus dilakukan secara terpadu dalam keseluruhan rantai pasok. Kata kunci: kelembagaan, tata niaga,  rantai nilai, telur, ayam kampung